Ortokeratoloģijas ietekme uz ceturtās kārtas aberācijām. - Rapisarda, Antonino Ivano (Latvijas Universitāte, 2020)
Maģistra darbs ir uzrakstīts angļu valodā uz 36 lapaspusēm. Tas satur 7 attēlus, 7 formulas, 7 tabulas, 3 grafikus un 38 literatūras atsauces. Darba mērķis bija novērtēt radzenes sagitālā augstuma un leņķa, kā arī ceturtās kārtas aberāciju izmaiņas pēc ortokeratoloģijas lēcu lietošanas. Pētījumā tika analizēti radzenes topogrāfijas dati, iegūti no 30 acīm, trīs mēnešus lietojot ortokeratoloģijas lēcas. Rezultāti neuzrādīja būtiskas izmaiņas ceturtās kārtas aberāciju lielumos. Modificējot ortokeratoloģijas lēcu parametrus, ir iespējams saglabāt labu redzes asumu un skotopisko redzi pēc ortokeratoloģijas lēcu lietošanas.

Thesis is written in English on 36 pages. It contains 7 figures, 7 equations, 7 tables, 3 graph and 38 references. The main purpose of this research was to compare the data of sagittal heights, sagittal angles before and after the nocturnal orthokeratology treatment and compare the variation of the IV order spherical aberration. The performance of the nocturnal orthokeratology treatment was evaluated by collecting data on 30 eyes via corneal topography over a period of 3 months. The sample of patients felt satisfied, because there were no changes in the IV order spherical aberration. From the first check, it is possible to better control the variation of spherical aberration of order IV, so as to be able to intervene by modifying lens design that will be ideal for the final result on visual acuity and its quality.
The Impact of Orthokeratology on the Fourth-Order Aberrations.
Keywords: Fizika; orthokeratology; contact lenses with inverse geometry; Baker’s Formula; IV order aberrations; visual acuity